Differences in help-seeking behaviour between males and females with multiple pelvic floor symptoms: A qualitative study - Kim Groot Wesseldijk; Hannah E. van Reemst; Ellen ter Horst; Grietje E. Knol-de Vries; Marco H. Blanker (Heliyon, 2024)
Background: Pelvic floor symptoms (PFS) are common and frequently co-occur, but few patients seek help despite negative effects on their quality of life. Moreover, most studies assessing help-seeking behaviour have only focused on a single PFS. Aim: We aimed to explore the barriers to and facilitators of help-seeking behaviour in males and females with at least two PFS. Design and Setting: This interview-based study included participants by age and symptoms (number and type) from a larger group taking part in a survey on PFS in the general population. Method: Two researchers independently encoded and analyzed the semi-structured interviews, which continued to saturation for both the male and female cohorts. Results: Of the 25 participants (13 male and 12 female), 9 sought help for all PFS, 10 did not seek help for any PFS, and 6 sought help for some PFS. We identified themes in domains related to the patient, healthcare professional, environment, and symptoms. Although most themes applied to both sexes, some had greater sex specificity. Conclusion: Males and females have more similarities than differences in help-seeking behaviour. Healthcare providers should know that patients who seek help for one symptom probably have multiple PFS that the patient has not reported.